The relationship between Stress, Strain and Social Capital - Martin Gächter; David A. Savage; Benno Torgler (University of Innsbruck, Department of Public Finance, 2010)
This paper analyzes the effectiveness of social capital in reducing the negative externalities associated with stress, as well as the physical and psychological strain indicators among police officers. Despite the fact that there is a large multidisciplinary literature on stress or on social capital, the link between both factors is still underexplored. In this empirical paper we therefore aim at reducing such a shortcoming. We focus on a strategically important work environment, namely law enforcement agents, that is not only characterized as physically and emotionally demanding, but also as an essential part for a well-functioning society due to the fact that inefficiencies in the police force can induce large negative externalities. Using a multivariate regression analysis focusing on eight different proxies for stress and strain, and two proxies for social capital and conducting several robustness checks, we find strong evidence that an increased level of social capital is correlated with a lower level of strain. From a policy perspective, our findings suggest that stress reduction programs should actively engage employees to build stronger social networks.
Keywords: I1; I31; J24; J81; Z13; 330; Social Capital; Trust; Stress and Strain; Gender; Police Officers; Burnout; Social Capital; Vertrauen; Stress; Soziales Netzwerk; Arbeitsbedingungen; Polizei; USA